2011
DOI: 10.1007/s00049-011-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 4-nerolidylcatechol by Heraclides brasiliensis (Lepidoptera: Papilionidae) reduces the toxicity of Piper umbellata (Piperaceae)

Abstract: Heraclides brasiliensis (Lepidoptera: Papilionidae) larvae feed preferably on Piperaceae, foraging successfully on leaf tissues even though species of this contain high levels of secondary metabolites such as amides and lignans, associated with diverse biological activities including insecticidal properties. Studies examining the metabolism of chemical constituents in Piperaceae by insects are rare. In this study, we characterized the metabolites of 4-nerolidylcatechol (4-NC), the major constituent of Piper um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Our study demonstrated similar results when evaluating the cytotoxic effect in K562 cells, a multi-drug resistant cell, after treatment with compounds (1), (3) and (5). In contrast, Ramos et al (2011) produced a derivative of compound (1) using the biotransformation of Heraclides brasiliensis (Lepidoptera: Papilionidae) larvae. This derivative showed a reduction of cytotoxicity when compared to the lead compound (1).…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated similar results when evaluating the cytotoxic effect in K562 cells, a multi-drug resistant cell, after treatment with compounds (1), (3) and (5). In contrast, Ramos et al (2011) produced a derivative of compound (1) using the biotransformation of Heraclides brasiliensis (Lepidoptera: Papilionidae) larvae. This derivative showed a reduction of cytotoxicity when compared to the lead compound (1).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, amides are generally associated to the chemical defense strategy in plants because of their potent insecticidal or repellent action against a broad range of insect species but, despite the variety of activities, their metabolic fate in insects is virtually unknown. Thus, as part of the study of metabolism of plant secondary compounds by insects, [19][20][21][22][23][24] herein we describe the metabolism of the major amides from leaves of P. tuberculatum by the insects Heraclides hectorides (Lepidoptera: Papilionidae) and Naupactus bipes (Coleoptera: Curculionidae), which are observed as herbivores of P. tuberculatum leaves in the field. For comparison purposes, four generalist herbivores Elaeochora trilineata (Orthoptera: Romaleidae), Chromacris speciosa (Orthoptera: Romaleidae), Tropidacris collaris (Orthoptera: Romaleidae) and Xyleus discoideus (Orthoptera: Romaleidae) were also offered leaves of P. tuberculatum to test the hypothesis that specialization on Piper hosts correlates with biotransformation of their toxic amides as a mechanism to circumvent toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Some phenolic compounds are sequestered and reused by larvae, e.g., as wing pigments of adult butterflies (Burghardt et al 1997(Burghardt et al , 2001. Certain phenolic compounds proceed intact through the digestive tract of lepidopterans, while others are chemically modified by the larvae (Ferreres et al 2008;Ramos et al 2012;Salminen et al 2004).…”
Section: Introductionmentioning
confidence: 99%